A Deep Learning–Based Framework for Supporting Clinical Diagnosis of Glioblastoma Subtypes - Munquad, Sana; Si, Tapas; Mallik, Saurav; Das, Asim Bikas; Zhao, Zhongming (Frontiers in Genetics, 2022)
Understanding molecular features that facilitate aggressive phenotypes in glioblastoma multiforme (GBM) remains a major clinical challenge. Accurate diagnosis of GBM subtypes, namely classical, proneural, and mesenchymal, and identification of specific molecular features are crucial for clinicians for systematic treatment. We developed a biologically interpretable and highly efficient deep learning framework based on convolutional neural network (CNN) for subtype identification. The classifiers were generated from high-throughput data of different molecular levels, i.e., transcriptome and methylome. Furthermore, an integrated subsystem of transcriptome and methylome data was also used to build the biologically relevant model. Our results showed that our deep learning model outperforms the traditional machine learning algorithms. Furthermore, to evaluate the biological and clinical applicability of the classification, we performed weighted gene correlation network analysis, gene set enrichment, and survival analysis of the feature genes. We identified the genotype-phenotype relationship of GBM subtypes and the subtype-specific predictive biomarkers for potential diagnosis and treatment.